The Influence of Thermal Insulation on Cooling a Residential Building in Khartoum (University of Khartoum Engineering Journal, 2022)
This paper aims to investigate and present energy saving techniques in buildings. In this study, the effect of thermal insulation on cooling a residential building in Khartoum was evaluated using Elite's Commercial Load Calculation Software (Chvac). A model design of a common one storey household was considered. Ten scenarios of different insulations or configurations were applied in the simulation. The cooling load of the building without insulation was found to be 47.48kW (13.5ToR). Using double glass pane windows, insulated walls and insulated roof reduced the cooling load to 29.54kW (8.4ToR) which translates into 38% reduction in electricity consumption.